Characterisation of the Pathogenicity of Beauveria sp. and Metarhizium sp. Fungi Against the Fall Armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae) - Nonthakorn (Beatrice) Apirajkamol; Bishwo Mainali; Phillip Warren Taylor; Thomas Kieran Walsh; Wee Tek Tay (Agriculture)
Previously, we assessed the pathogenicity of eleven endemic entomopathogenic fungi (EPF), including six Beauveria isolates, four Metarhizium isolates, and one M. pingshaense, against the agricultural pest Spodoptera frugiperda (fall armyworm, FAW). We found that four Beauveria and one Metarhizium isolates were effective, with Beauveria isolates B-0571 and B-1311 exhibiting high mortality within 24 h post-spore application. This study aimed to identify and characterise the entomopathogenesis mechanisms of these isolates as potential FAW biocontrol agents. All Beauveria isolates were determined as B. bassiana, the Metarhizium isolates as two M. robertsii, one M. majus, and an unknown Metarhizium species. Despite the high mortality from B-0571 and B-1311 isolates, scanning electron microscopy showed no fungal spore germination on dead larvae 24 h after spore application. Four insecticide compound gene clusters, i.e., bassianolide, beauvericin, beauveriolide, and oosporein, were identified and characterised in all B. bassiana isolates. These compounds are hypothesised to contribute to the high early mortality rates in FAWs. Identifying and characterising gene clusters encoding these insecticide compounds in B-0571 and B-1311 will contribute to a better understanding of the entomopathogenicity of these isolates that will be vital to developing these EPF isolates as sustainable alternative FAW biocontrol agents.